Cool Japan Guide Fun in the Land of Manga, Lucky Cats and Ramen - Denson, Abby (Perseus Book Group, 2015)
Explores Japan, offering travel tips and recommendations for dining, sights, and activities.
Lulu Award-winner Abby Denson has scripted for The Amazing Spider-man, The Powerpuff Girls and other comics. Her graphic novel Dolltopia won a Bronze International Manga Award and the Moonbeam Children's Book Award. Her popular blog The City Sweet Tooth is an online tour of New York's best bakeries, pastry shops, and cafes. You can view her work at abbycomix.com and citysweettooth.com.